SOUTH AFRICAN CONSTITUTION AND CONFLICTUAL DEMOCRACY - Botha, Henk. Link ([S.l.])
1 online resource
Keywords: Human dignity, equality, and freedom are central to the South African Constitution. This book examines these values through a conflictual democratic lens, which views conflict, power, and disagreement as constitutive of democracy. The book explores the capacity of value-based constitutional interpretation to create openings for democratic dialogue and emancipatory social struggles. Conversely, it also assesses the ability of constitutional interpretation to normalise and depoliticise domination, inequality, and exclusion. The book uses a conflictual frame to shed light on the interplay between the universality of dignity, equality, and freedom and the particularity of the discourses and conventions that mediate their interpretation and enforcement. It argues that such a frame could enable realistic assessments of the ability of the constitutional order to safeguard spaces for emancipatory struggles and respond to radical demands for the reconstitution of society. Drawing on the text of the Constitution, case law, academic commentary, and constitutional, political, and critical legal theory, this book will be an important read for researchers of constitutional law and critical legal theory, both within South Africa and beyond. Henk Botha is a Professor in the Faculty of Law, Stellenbosch University, South Africa.